Analysis Of The Influence Of Economic Factors On The Divorce Rate In Gorontalo Province - Suriyanti Dama; Sri Endang Saleh; Irawati Abdul (STIE Amkop Makassar, 2026)
This study examines the partial and simultaneous effects of unemployment, education, and poverty on divorce rates in Gorontalo Province. Using an associative quantitative approach, the research analyzes seven years of secondary time-series data (2018–2024) obtained from the Central Statistics Agency (BPS) of Gorontalo Province. The study applies panel data regression to evaluate relationships among variables. The findings show that unemployment significantly influences divorce rates, indicating that higher unemployment is associated with a greater likelihood of divorce. Education level has a significant negative effect, meaning higher educational attainment tends to reduce divorce occurrences. Poverty demonstrates a significant positive effect, suggesting increased poverty elevates divorce risk. Simultaneously, unemployment, education, and poverty jointly exert a significant influence on divorce rates, confirming that divorce represents a multidimensional social phenomenon shaped by interacting economic and social conditions over time. These results highlight the importance of integrated policy interventions, including employment expansion, educational improvement, and poverty alleviation programs, to reduce family instability. Future research is recommended to incorporate cultural and psychological variables to better understand regional variations in marital dissolution.